2013
DOI: 10.1371/journal.pone.0062103
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate 2 Is Required for Testicular Development

Abstract: Insulin receptor substrate (IRS) proteins are key mediators of insulin and insulin-like growth factor (IGF) signalling. In mice, deletion of Irs1 is associated with profound growth retardation and increased longevity whereas Irs2-deficiency causes diabetes and female infertility. Clinical studies suggest that diabetes and obesity diminish male fertility. However, the role of IRS proteins in male reproduction is unknown. We observed that testis weight is reduced by 45% in Irs2-deficient mice as compared with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
0
29
0
1
Order By: Relevance
“…Our results showed decreased testicular weights (26%) in all diabetic mice. Similarly, in adult IRS2 (Insulin Receptor Substrate 2) deficient mice (8-12 weeks of age), reduced testicular weight (45%) was reported (Griffeth et al, 2013). Furthermore, reduced testicular weights were also observed in Akita homozygous mice at the age of 9 weeks (Schoeller et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Our results showed decreased testicular weights (26%) in all diabetic mice. Similarly, in adult IRS2 (Insulin Receptor Substrate 2) deficient mice (8-12 weeks of age), reduced testicular weight (45%) was reported (Griffeth et al, 2013). Furthermore, reduced testicular weights were also observed in Akita homozygous mice at the age of 9 weeks (Schoeller et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Finally, KO studies focused on insulin superfamily members (Baker et al 1996, Burnicka-Turek et al 2012, their receptors (Nef et al 2003) or on intermediaries of insulin signaling pathway (Griffeth et al 2013), provided further data supporting the importance of insulin signaling pathway on the male reproductive function, namely on testicular aspects and sperm characteristics (Baker et al 1996, Burnicka-Turek et al 2012, Griffeth et al 2013 as well as on male sex determination during development (Nef et al 2003) are present.…”
Section: Insulin and Male Reproductive Functionmentioning
confidence: 96%
“…Testosterone is responsible for regulating and maintaining growth and proper functioning of the reproductive organs [42,43]. Testicular size has been directly linked to spermatogenesis and sperm quality [44,45]. In this study it was observed that there was a significant decrease in body weights after the 6 week period in the diabetic control group when compared to the normal control group as well as when compared to their initial weights.…”
Section: Group/ Treatmentsmentioning
confidence: 63%